Case studies on decision for cervical cancer screening among working women - Baharom, Anisah; Ismail, Maimunah (The Journal of Human Resource and Adult Learning (HRAL), 2008)
This study aimed at exploring working women’s perception on factors that influence their decision for cervical cancer screening or pap test. Specifically, this study looked at the influence of gender relations and gender roles among married working women in relation to the perception. This qualitative study was conducted with three women cases based on in-depth interviews. They represented three different cervical cancer screening behaviors which are, had regular pap smear, had pap smear but irregularly and never had pap smear. The study concluded that although gender relations between husband and wife is of egalitarian type, i.e. women have the freedom of movement, empowered to make decision and financial freedom, these did not guarantee that they would practice preventive health care. Recommendations for practice and further research are put forth.